LI ZEHOU’S VIEW ON CHINESE MODERNIZATION AND THE PRECARIOUS RELATIONSHIP BETWEEN MARX AND CONFUCIUS - Rošker, Jana S. Rošker (Problemos, 2016)
Li Zehou is one of the most significant and influential Chinese philosophers of our time and one of the rare Chinese intellectuals whose work has acquired a wide readership abroad. He dedicated himself to the task of finding a sensible, suitable way of harmonizing past and present, tradition and modernity, China and the West. In this context, he tried to create a synthesis between early Marxist and classical Confucian discourses. Through a critical analysis of these attempts, the present article reveals some crucial theoretical problems underlying such efforts. Considering the fact that in contemporary China, the link between Confucian and Marxist philosophy is a much discussed (and rather controversial) topic, the paper also represents a contribution to the clarification of this topical problem.
Keywords: Li Zehou; Confucius; Confucian revival; Marx; methodology of Chinese philosophy